Elucidation of crystal growth, structural characterization, thermal properties, and molecular dynamics using NMR near phase transition temperature of [N(CH3)4]2CoCl4 - Changyub Na; Ae Ran Lim (Scientific Reports)
Abstract This discussion explores various facets of recently elucidated characteristics of [N(CH3)4]2CoCl4 single crystals. Phase transitions were identified at 196, 276, and 293 K, and thermodynamic stability was observed up to 640 K. With increasing temperature, the crystal structures of phases III, II, and I were monoclinic, orthorhombic, and orthorhombic, respectively. In addition, the nuclear magnetic resonance (NMR) chemical shifts of 1H, 13C, and 14N were analyzed to elucidate the structural geometry near TC. In phases I and II, two 13C NMR signals were observed that may be attributed to the different N(1)(CH3)4 and N(2)(CH3)4 sites, whereas, in phase III, four 13C NMR signals were observed that may be attributed to the six different N(CH3)4 sites. By contrast, because the spin of 14N is I = 1, two signals are generally expected, however, in phase I, four signals were observed owing to the different N(1)(CH3)4 and N(2)(CH3)4 sites. In phase III, 12 signals were observed because six different N sites were present. The results of the 13C and 14N NMR indicate that the transition from phase I to phase III involves a decrease in the symmetry of the crystal structure. The temperature dependences of the relaxation times T1 and T1ρ in the laboratory and rotating frame for1H enabled the estimation of the activation energies for the molecular motion of the N(CH3)4 groups.